Determination of polyphenolic content of bark extracts for wood adhesives - Md. Tahir, Paridah; Musgrave, Oliver C.; Ashaari, Zaidon (Walter de Gruyter, 2002)
The phenolic content of condensed tannins varies considerably, depending on the method of determination. Even though the Stiasny precipitation number has been commonly used to estimate the amount of reactive tannin towards formaldehyde, particularly in adhesive applications, this estimation alone is not sufficient. In this study two methods of determining the amount of reactive tannin towards formaldehyde were examined. These were (1) the reactivity towards formaldehyde or the Stiasny precipitation number, and (2) the formaldehyde uptake. Five different types of tannin were examined from Rhizophora mucronata, P. radiata, mimosa, quebracho and chestnut. The study indicates that the phenolic content in tannin can be better estimated by determining both the Stiasny number and the amount of formaldehyde uptake. High correlation (r2 = 0.905) was detected between the two methods. The study also revealed that hot water extracts of R. mucronata contain relatively small amounts of reactive polyphenols and are less reactive than sulfite extracts. The consumption of formaldehyde by this type of tannin was only 0.294 molecules per flavanoid unit. Similar to R. mucronata, the sulfite extracts of P. radiata contain relatively high amounts of reactive polyphenols and reacted with substantially higher amounts of formaldehyde per flavanoid unit, comparable to mimosa and quebracho tannins. Nonetheless, the reactivity towards formaldehyde (gel time) of the latter tannins is much lower, despite their higher polyphenolic content. Of the two methods used to estimate the polyphenolic content of bark extracts, the Stiasny number had a relatively higher correlation (r2 = 0.518) with gel time than formaldehyde uptake (r2 = 0.345) did. The behaviour of these tannins in relation to their reactivity and chemical structures is discussed.